2011
DOI: 10.1371/journal.pone.0022489
|View full text |Cite|
|
Sign up to set email alerts
|

Pathogenic LRRK2 Mutations Do Not Alter Gene Expression in Cell Model Systems or Human Brain Tissue

Abstract: Point mutations in LRRK2 cause autosomal dominant Parkinson's disease. Despite extensive efforts to determine the mechanism of cell death in patients with LRRK2 mutations, the aetiology of LRRK2 PD is not well understood. To examine possible alterations in gene expression linked to the presence of LRRK2 mutations, we carried out a case versus control analysis of global gene expression in three systems: fibroblasts isolated from LRRK2 mutation carriers and healthy, non-mutation carrying controls; brain tissue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
2
23
1
Order By: Relevance
“…These findings indicate a concerted regulation of these PARK-genes in SN DA neurons in PD, as a protective response to increased proteasomal and lysosomal and/or autophagosomal demands. The finding that LRRK2 (PARK8) mRNA levels were not altered in remaining DA neurons from PD brains is in accordance with a study showing that pathogenic LRRK2 mutations do not alter gene expression in human brain tissue (Devine et al., 2011a). Increased expression of wild-type LRRK2 accelerates alpha-synuclein-induced neurodegeneration and is thus not expected as an allostatic survival mechanism of SN DA neurons in PD (Caguci, 2003; Lin et al., 2009).…”
Section: Discussionsupporting
confidence: 91%
“…These findings indicate a concerted regulation of these PARK-genes in SN DA neurons in PD, as a protective response to increased proteasomal and lysosomal and/or autophagosomal demands. The finding that LRRK2 (PARK8) mRNA levels were not altered in remaining DA neurons from PD brains is in accordance with a study showing that pathogenic LRRK2 mutations do not alter gene expression in human brain tissue (Devine et al., 2011a). Increased expression of wild-type LRRK2 accelerates alpha-synuclein-induced neurodegeneration and is thus not expected as an allostatic survival mechanism of SN DA neurons in PD (Caguci, 2003; Lin et al., 2009).…”
Section: Discussionsupporting
confidence: 91%
“…It was found that transcription activity was upregulated in G2019S mice compared to knockout and wild-type when each LRRK2 condition was overexpressed. This suggests that LRRK2 has some function or influence on the transcription process (Nikonova et al 2012), although again the data on this are conflicting (Devine et al 2011). …”
Section: Proximal Signalling Eventsmentioning
confidence: 99%
“…13 Recently, it could be demonstrated that overexpression of leucine-rich repeat kinase 2 (LRRK2) does not result in altered gene expression in HEK293 cells. 15 Mutations in LRRK2 are strongly associated with late-onset autosomal dominant PD, and HEK293 may be suitable to go for candidate pharmacological screening for LRRK2 inhibitors. 16 Moreover, mechanisms of possible in vitro transfer of aSyn and its modified species may be studied in this cell line.…”
Section: Parkinson's Diseasementioning
confidence: 99%